Ultra-thin metal fast-assembly plate and forming preparation method thereof
Patent Information
- Application Number
- CN202611175821.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明解决的技术问题在于现有金属复合板件在连续化生产中,胶黏剂热压固化周期长导致无法快速脱模定型,且板材在出料降温阶段易因上下表面温差和收缩率不一致产生翘曲变形,此外,芯材与金属基板的界面剥离强度在自然老化过程中也容易出现衰减,同时,本发明旨在重点解决超薄金属板(超薄镀锌板或薄铝)在传统模压、辊压加工工艺中极易发生的拉伸断裂问题,突破超薄材料的成型瓶颈
[0064]1.本发明的成型制备方法通过热压与强制冷压交替的工序安排,改善了连续化生产中板材易翘曲变形的问题。热压复合后的板材直接进入带有循环冷却水的冷压工位,受压状态下的强制降温促使胶层内的聚己内酯链段快速相变结晶,体系由粘流态转为玻璃态并建立初粘力。该工艺在锁定多层材料相对位置的同时,抵消了金属面板与平衡铝箔因降温收缩率不同而产生的不对称热应力,降低了脱模后板材发生宏观弓形翘曲的概率。
Smart Images

Figure CN122976134A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building decoration materials technology, specifically to ultra-thin metal quick-assembly panels and their forming and preparation methods. Background Technology
[0002] Metal composite panels are widely used in interior decoration and partition projects due to their lightweight, flame-retardant properties, and good surface finish. Existing quick-assembly metal panels typically use thin metal sheets as the surface layer, filled with inorganic materials as the core layer, and are composited and shaped using adhesives in a hot press. To enable rapid assembly of the panels on-site, the edges of the metal panels are usually bent to create corresponding assembly grooves.
[0003] In continuous production processes, the molding of multilayer heterogeneous composite panels faces the engineering challenge of uneven thermal stress release. The metal panel and the inorganic porous core material differ in thermal conductivity and coefficient of thermal expansion. After high-temperature hot-pressing, the volume shrinkage rates of each layer during natural cooling are not consistent. Conventional adhesives require a long curing time after hot pressing to establish sufficient cohesive strength. At this point, the not-fully-cured bonding interface is unable to resist the asymmetric shrinkage stress between the upper and lower layers, leading to warping and deformation of the panel after demolding, affecting the flatness of the finished product.
[0004] Furthermore, when dealing with inorganic porous core materials, conventional polyurethane adhesives rely primarily on physical pore anchoring for interfacial bonding. Under long-term changes in environmental temperature and humidity, the interfacial peel strength is prone to decrease. Simultaneously, to meet the demands for lightweighting and cost reduction, metal panel substrates are trending towards ultra-thin designs. This makes pre-bent splicing grooves susceptible to localized deformation or collapse when subjected to the vertical pressure of the hot-pressing composite process. This results in deviations in the groove dimensions of the finished panels, reducing on-site assembly accuracy and splicing decorative effects. More importantly, the field is working to overcome the application bottlenecks of ultra-thin galvanized sheets or thin aluminum. Existing technologies, when using traditional molding and roll forming for ultra-thin sheets (such as 0.18mm and below), are prone to stress concentration and tensile fracture due to the extremely thin material and large localized deformation. This severely impacts the yield and mass production feasibility of ultra-thin metal quick-assembly panels. Summary of the Invention
[0005] The technical problem solved by this invention is that in the continuous production of existing metal composite plates, the long hot-press curing cycle of adhesives makes it impossible to quickly demold and shape them. In addition, the plates are prone to warping and deformation during the cooling stage due to the temperature difference and shrinkage rate of the upper and lower surfaces. Furthermore, the interfacial peel strength between the core material and the metal substrate is also prone to decay during natural aging. At the same time, this invention aims to solve the problem of tensile fracture that is very easy to occur in the traditional molding and rolling processes of ultra-thin metal plates (ultra-thin galvanized plates or thin aluminum), and break through the forming bottleneck of ultra-thin materials.
[0006] To address the above problems, the present invention provides the following technical solution:
[0007] In a first aspect, the present invention provides an ultra-thin metal quick-release plate, which adopts the following technical solution:
[0008] An ultra-thin metal quick-installation plate, from top to bottom, includes a decorative film layer, an aluminum-zinc plate or a thin aluminum layer, an upper adhesive layer, an inorganic bubble board core material layer, a lower adhesive layer, and a balancing aluminum foil layer.
[0009] Both the upper and lower adhesive layers are made of polymer composite hot-press adhesive, which is composed of the following raw materials in parts by weight:
[0010] 30-40 parts of polypropylene glycol;
[0011] 20-30 parts of polycaprolactone diol;
[0012] 15-25 parts of 4,4'-diphenylmethane diisocyanate;
[0013] - 1 to 3 parts of glycidyl etheroxypropyltrimethoxysilane;
[0014] 0.01 to 0.05 parts of dibutyltin dilaurate.
[0015] By adopting the above technical solution, the polymer composite hot-press adhesive plays a role in bonding and shaping within the multilayer board structure.
[0016] Specifically, the polypropylene glycol in the formulation provides flexible segments, and the polycaprolactone glycol provides crystalline segments. Combined with a silane coupling agent, the colloid possesses curing properties that combine physical crystallization and chemical crosslinking.
[0017] During the polyurethane prepolymer synthesis stage, the polyol undergoes an addition polymerization reaction with an excess of 4,4'-diphenylmethane diisocyanate to generate a prepolymer backbone with isocyanate groups at the ends. Specifically, the terminal hydroxyl groups of the diol react with the diisocyanate groups to form urethane bonds.
[0018] When the composite adhesive is heated, it is in a molten state and can penetrate into the micropores on the surface of the inorganic bubble board core material;
[0019] During the subsequent cooling and setting process, the polycaprolactone crystalline segments in the prepolymer backbone rapidly arrange themselves in a regular pattern and crystallize as the temperature decreases, causing the colloidal modulus to rise sharply, thereby generating initial adhesion and locking the structural stress between the metal panel and the core material.
[0020] During the subsequent environmental storage phase, the isocyanate groups at the ends of the prepolymer absorb moisture from the air and the core material, undergoing a hydrolysis reaction to generate carbamic acid. Because carbamic acid is unstable, it will decompose and release carbon dioxide. .
[0021] The generated free primary amine groups then undergo chain extension and crosslinking reactions with the unreacted isocyanate groups. This forms a urea bond crosslinking network. At the same time, the methoxy group in γ-glycidyl etheroxypropyltrimethoxysilane undergoes hydrolysis and condensation with water, forming siloxane chemical bond crosslinking points at the interface of the inorganic bubble board core material.
[0022] This combination of physical and chemical anchoring methods can usually effectively alleviate the peeling stress between interfaces.
[0023] Hydrogen peroxide aqueous solution decomposes and releases oxygen under stirring and alkaline conditions, forming a closed-cell bubble network inside the matrix.
[0024] In this process, calcium stearate plays a role in stabilizing foam, polyvinyl alcohol improves the viscosity of the slurry and coats the foam pore walls, while alkali-free chopped glass fibers dispersed in the crystalline phase play a bridging and crack-preventing role.
[0025] The core material formed by this formulation system has corresponding compressive strength and cohesive strength, which is beneficial for withstanding the load impact of subsequent hot pressing and cold pressing processes.
[0026] Preferably, the polymer composite hot-press adhesive is prepared by the following method:
[0027] A specific weight portion of polypropylene glycol is mixed with polycaprolactone glycol and dehydrated under vacuum conditions;
[0028] A specific weight part of 4,4'-diphenylmethane diisocyanate was added under nitrogen protection and reacted at a constant temperature to obtain a polyurethane prepolymer with isocyanate-terminated groups.
[0029] After cooling, a specific weight of γ-glycidyl etheroxypropyltrimethoxysilane and dibutyltin dilaurate are added, and the mixture is stirred at a constant temperature and degassed under vacuum to obtain the final product.
[0030] By adopting the above technical solution, the water carried in the polyol raw material is removed by vacuum dehydration in the early stage, which helps to reduce the early consumption of isocyanate groups and the risk of gelation in the synthesis stage.
[0031] Considering the need for crosslinking in the later stages, dibutyltin dilaurate catalyst was added at the end of the reaction to provide the required hydrolysis crosslinking catalytic activity for the system. In addition, the vacuum degassing treatment at the end was mainly used to remove air bubbles entangled in by stirring, which improved the uniformity and continuous film formation of the subsequent adhesive coating to some extent.
[0032] Preferably, the two ends of the aluminized zinc plate or thin aluminum layer are provided with a double mother groove structure formed by pre-bending inward and naturally springing back, and the inner gap of the double mother groove structure is filled with aluminum strips.
[0033] Furthermore, the thickness of the aluminized zinc plate or thin aluminum layer is 0.18 mm, the gap of the double female groove structure is 1.8 to 2.0 mm, and the cross-sectional thickness of the aluminum strip is 1.7 to 1.9 mm.
[0034] By adopting the above technical solution, the double-groove structure provides a positioning and concealed installation channel when splicing panels.
[0035] The aluminum strips pre-filled in the gaps fill the air gaps in the bending section of the thin metal sheet, providing solid support for the bending point.
[0036] When the sheet metal is subjected to hot and cold pressing loads, the aluminum strip can bear and transmit the longitudinal vertical stress at the edge, reducing the probability of deformation and inward collapse of the double female groove under pressure, and playing a positive role in maintaining the consistency of the groove size of the end sheet metal.
[0037] Secondly, the present invention provides a method for molding and preparing an ultrathin metal quick-assembly plate, which adopts the following technical solution:
[0038] A method for forming and preparing an ultrathin metal quick-release plate includes the following steps:
[0039] Cold-press and pre-bend both ends of the aluminized zinc plate or thin aluminum, and after springback, form a double female groove structure. Then push the aluminum strip into the inner gap of the double female groove structure to fill it.
[0040] The polymer composite hot-press adhesive is heated and melted, and then the adhesive liquid is simultaneously rolled onto the upper and lower surfaces of the inorganic bubble board core material.
[0041] The treated aluminized zinc plate or thin aluminum is laid flat on the front side of the inorganic bubble board core material, and the balancing aluminum foil is laid flat on the back side of the inorganic bubble board core material. They are then simultaneously fed into a flat plate hot press for pressure holding and hot pressing composite.
[0042] After demolding, it enters the cold pressing station, where it is pressed and shaped by a cold pressing mold with circulating cooling water.
[0043] A decorative film is applied to the front of the cold-pressed and shaped aluminized zinc plate or thin aluminum using a PUR coating process; the coated plates are then stacked and transferred to a room temperature environment for storage to allow for internal moisture cross-linking and curing.
[0044] By adopting the above technical solution, during the hot pressing stage, due to the application of temperature and uniform pressure to the front aluminum-zinc plate or thin aluminum and the back balanced aluminum foil, the polymer composite hot pressing adhesive is in a low viscosity fluid state and is pressed into the pore microstructure on the surface of the inorganic bubble board core material, forming an interlocking anchoring effect.
[0045] The sheet material then leaves the hot press mold and enters the cold press station, where it is cooled and kept under pressure by the cold press mold with cooling circulating water.
[0046] Forced cooling causes the polycaprolactone segments in the adhesive layer to undergo a phase transition and crystallize, transforming the system from a viscous flow state to a glassy state. The adhesive layer loses its fluidity and develops initial tack strength.
[0047] Since each layer of the sheet is physically anchored, forced pressure cooling helps resist the asymmetric thermal shrinkage stress of the front metal panel and the back aluminum foil during the cooling process, thereby reducing the risk of macroscopic warping caused by asymmetric shrinkage.
[0048] Meanwhile, the establishment of initial adhesion strength allows the demolded boards to immediately enter the cold lamination process, reducing offline waiting time and facilitating continuous operation of the production line.
[0049] The subsequent room temperature and humidity crosslinking process utilizes the ambient humidity to drive the prepolymer to undergo a network crosslinking reaction, transforming the bonding interface from initial physical anchoring to chemical bonding.
[0050] Preferably, a flexible flip-plate bending machine is used for cold pre-bending, and the bending angle of the flip plate of the bending machine relative to the unbent plane is set to 92°~93°.
[0051] By adopting the above technical solution, the bending angle of more than 90° compensates for the elastic recovery deformation of the cold-worked parts of galvanized steel sheets or thin aluminum after unloading the bending moment.
[0052] This helps maintain the theoretical gap between the two wings of the double mother groove formed after natural springback, which is convenient for the subsequent insertion of aluminum strips and, to a certain extent, maintains the dimensional stability of the outer corner after the substrate is formed.
[0053] Preferably, the heating and melting temperature of the polymer composite hot press adhesive is 110~130℃, and the coating amount on each surface is controlled at 80~120g / m².
[0054] The surface temperature of the hot platen of the flat platen hot press is 110~130℃, the applied pressure is 0.8~1.5MPa, and the holding time is 10~15s.
[0055] By adopting the above technical solution, the heating and hot pressing temperature of 110~130℃ can melt the crystalline chain segments and activate the leveling properties of the adhesive, and this temperature range usually does not cause significant damage to the crystal water of the hydrated skeleton phase inside the inorganic bubble board core material.
[0056] The matching pressure of 0.8~1.5MPa and holding time of 10~15s can not only squeeze the adhesive into the inorganic pores, but also avoid the inorganic core material skeleton from being crushed and broken due to excessive pressure.
[0057] Preferably, the temperature of the circulating cooling water introduced into the cold pressing mold is 15~25℃, the pressure applied at the cold pressing station is 1.0~2.0MPa, and the cold pressing time is 5~10s.
[0058] By adopting the above technical solution, the circulating water at 15~25℃ and the pressure holding at 1.0~2.0MPa work together to remove the heat accumulated inside the plate by utilizing the thermal conductivity of the metal.
[0059] During the 5-10s contact time, the adhesive temperature crosses the crystallization temperature of the polycaprolactone chain segments, causing the polymer chains to crystallize under a confined state, which plays a solidifying role in calibrating the flatness of the board.
[0060] Preferably, the temperature of the storage environment is controlled at 15~35℃, the relative humidity is controlled at 40%~70%, and the storage time is 10~12h.
[0061] By adopting the above technical solution, a stable environmental temperature and humidity field provides suitable conditions for the reaction between isocyanate groups and moisture inside the board.
[0062] The storage time of 10 to 12 hours allows the carbon dioxide byproducts generated by the reaction to escape and diffuse along the interface of the loose core material, reducing the probability of foaming inside the adhesive layer, thereby obtaining a relatively dense cross-linked network.
[0063] This invention provides an ultrathin metal quick-assembly plate and its molding and preparation method. It has the following beneficial effects:
[0064] 1. The molding and preparation method of this invention improves the problem of easy warping and deformation of sheet materials in continuous production by alternating hot pressing and forced cold pressing processes. After hot pressing and lamination, the sheet material directly enters the cold pressing station with circulating cooling water. The forced cooling under pressure promotes the rapid phase change and crystallization of polycaprolactone segments in the adhesive layer, and the system changes from a viscous flow state to a glassy state and establishes initial adhesion. This process, while locking the relative positions of the multilayer materials, offsets the asymmetric thermal stress caused by the different shrinkage rates of the metal panel and the balancing aluminum foil due to cooling, reducing the probability of macroscopic bow-shaped warping of the sheet material after demolding.
[0065] 2. The polymer composite hot-press adhesive used in this invention combines a dual curing mechanism of physical crystallization and chemical crosslinking, which helps maintain the long-term stability of interfacial bonding strength. During the cold pressing stage, the crystallization of polycaprolactone segments provides early shaping strength, meeting the cycle requirements of rapid demolding and cold film application on the production line. In the subsequent room temperature storage stage, the terminal isocyanate groups absorb moisture and undergo chain extension reactions to form a urea bond network. The methoxy groups of the silane coupling agent undergo hydrolysis and condensation with the inorganic core material interface to form siloxane chemical bonds. This chemical bonding method slows down the attenuation of interfacial peel strength during natural aging.
[0066] 3. The edge of the sheet metal in this invention adopts a double-groove structure with an inner aluminum profile, successfully breaking through the technical bottleneck of ultra-thin sheet forming and solving the problem of tensile fracture of ultra-thin metal sheets (ultra-thin galvanized sheets or thin aluminum) during conventional pressing and rolling processes. After the galvanized sheet or thin aluminum is flexibly pre-bent, the aluminum profile pushed into the gap fills the gap in the bending section, providing rigid solid support when bearing the vertical load of the hot and cold pressing processes. This process and structure combination avoids damage to the ultra-thin sheet caused by excessive stretching, and at the same time prevents the thin-walled groove from deforming and collapsing inward under pressure, thereby ensuring the uniformity of the gaps and the installation accuracy of the final sheet metal during splicing and assembly. Attached Figure Description
[0067] Figure 1 The graph shows the thermal analysis and group conversion rate test results of the polymer composite hot-press adhesive of this invention.
[0068] in, Figure 1 Figure a shows the differential scanning calorimetry (DSC) cooling curve of the polymer composite hot-press adhesive in the example. Figure 1 Figure b shows the relationship between the relative absorbance decay and conversion rate of isocyanate groups in the adhesive layer under different storage times.
[0069] Figure 2 This is a comparative schematic diagram showing the shrinkage strain changes on the front and back sides of the sheet during the molding process of this invention;
[0070] in, Figure 2 Figure a shows the thermal strain curves of the front and back sides during the entire cooling and shaping cycle of the example. Figure 2 b is a comparative example of the thermal strain curves of the front and back sides under the secondary hot-pressing composite process.
[0071] Figure 3 This is a schematic diagram of cross-sectional measurement of the forming accuracy of the sheet metal and the dimensional stability of the mother groove according to the present invention;
[0072] in, Figure 3 Image a is a cross-sectional scan of the double-groove structure formed in the embodiment and supported by aluminum strips. Figure 3 b is a comparative diagram showing the wall thickness reduction at the outer rounded corner of the bend using a multi-pass cold bending and rolling process.
[0073] Figure 4 This is a three-dimensional contour scan of the macroscopic flatness and warping deformation of the large plate of the present invention;
[0074] in, Figure 4 a is a three-dimensional elevation profile of the molded sheet prepared in the example. Figure 4 b is a three-dimensional elevation profile of the macroscopic bow-shaped warping of the board prepared for comparison.
[0075] Figure 5This is a schematic diagram comparing the interfacial peel strength and high and low temperature weathering aging test results of the present invention.
[0076] in, Figure 5 a is a bar chart comparing the 90° peel strength of each group in the initial state and after aging cycles. Figure 5 b is a comparison diagram of the failure modes of core material cohesive failure and metal interface debonding after peeling test.
[0077] Figure 6 This is a schematic diagram of the structure of the ultra-thin metal quick-release plate of the present invention;
[0078] in, Figure 6 a is an overall perspective view of the ultra-thin metal quick-assembly plate of the present invention. Figure 6 b is a cross-sectional view of the end of the ultra-thin metal quick-release plate of the present invention.
[0079] Figure 7 This is a schematic diagram of the continuous forming process for the ultrathin metal quick-assembly plate of the present invention. Detailed Implementation
[0080] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0081] The main raw materials and reagents used in the following examples and comparative examples are as follows. Unless otherwise specified, all chemical reagents are commercially available analytical grade or higher grade products, and all industrial raw materials are commercially available products.
[0082] The aluminum-zinc plate or thin aluminum sheet with a thickness of 0.18 mm has a surface coating composition of 55% aluminum, 43.4% zinc and 1.6% silicon by mass.
[0083] Polypropylene glycol, CAS No. 25322-69-4, functionality 2, homopolymer arrangement of repeating units, weight average molecular weight The value is 2000, and the hydroxyl value ranges from 53 mg KOH / g to 59 mg KOH / g.
[0084] Polycaprolactone diol, CAS No. 36890-68-3, is a homopolymer with repeating units arranged in a homopolymer state. It is solid at room temperature and has a weight-average molecular weight of [missing information]. It has a value of 2000, a melting point of 40℃ to 50℃, and a hydroxyl value ranging from 53 mg KOH / g to 59 mg KOH / g.
[0085] Balanced aluminum foil, pure aluminum foil with a thickness of 0.03 mm to 0.08 mm.
[0086] The aluminum profile is made of 6063 aluminum alloy and has a cross-sectional thickness of 1.7mm to 1.9mm.
[0087] Polyvinyl chloride decorative film, a polyvinyl chloride homopolymer film with a thickness of 0.12 mm to 0.18 mm.
[0088] In the following embodiments, the length and width of the inorganic bubble board core material are cut according to the design dimensions of the target quick-installation board and adapted to the composite area of the aluminized zinc steel plate or thin aluminum.
[0089] The thickness of the inorganic bubble board core material is determined based on the design thickness of the target quick-assembly board.
[0090] Preparation Example 1:
[0091] See attached document Figure 7 This preparation example provides a method for preparing a polymer composite hot-press adhesive, including the following steps:
[0092] 35 parts by weight of polypropylene glycol and 25 parts by weight of polycaprolactone glycol were added to a reaction vessel equipped with a mechanical stirrer and dehydrated for 1.5 h at 105 °C and a vacuum gauge pressure of -0.09 MPa, and then cooled to 80 °C.
[0093] Under nitrogen protection, 20 parts by weight of 4,4'-diphenylmethane diisocyanate were added to the reactor, the temperature was raised to 85°C, and the reaction was carried out at a constant temperature for 2.5 h to obtain a polyurethane prepolymer with terminal isocyanate groups.
[0094] Cool the reaction system to 75°C and add 2 parts by weight. - Glycidyl ether oxypropyltrimethoxysilane and 0.03 parts by weight of dibutyltin dilaurate were stirred at a constant temperature for 30 minutes. After completion, the mixture was degassed under vacuum for 15 minutes and then filled into a sealed container under nitrogen pressure to obtain a polymer composite hot press adhesive.
[0095] Preparation Example 2:
[0096] This preparation example provides a method for preparing a polymer composite hot-press adhesive, including the following steps:
[0097] 30 parts by weight of polypropylene glycol and 20 parts by weight of polycaprolactone glycol were added to a reaction vessel equipped with a mechanical stirrer and dehydrated for 1.0 h at 100 °C and a vacuum gauge pressure of -0.08 MPa, and then cooled to 70 °C.
[0098] Under nitrogen protection, 15 parts by weight of 4,4'-diphenylmethane diisocyanate were added to the reactor, the temperature was raised to 80°C, and the reaction was carried out at a constant temperature for 2.0 h to obtain a polyurethane prepolymer with terminal isocyanate groups.
[0099] Cool the reaction system to 75°C and add 1 part by weight. - Glycidyl ether oxypropyltrimethoxysilane and 0.01 parts by weight of dibutyltin dilaurate were stirred at a constant temperature for 30 minutes. After completion, the mixture was degassed under vacuum for 15 minutes and then filled into a sealed container under nitrogen pressure to obtain a polymer composite hot press adhesive.
[0100] Preparation Example 3:
[0101] This preparation example provides a method for preparing a polymer composite hot-press adhesive, including the following steps:
[0102] 40 parts by weight of polypropylene glycol and 30 parts by weight of polycaprolactone glycol were added to a reaction vessel equipped with a mechanical stirrer and dehydrated for 2.0 h at 110 °C and a vacuum gauge pressure of -0.10 MPa, and then cooled to 90 °C.
[0103] Under nitrogen protection, 25 parts by weight of 4,4'-diphenylmethane diisocyanate were added to the reactor, the temperature was raised to 90°C, and the reaction was carried out at a constant temperature for 3.0 h to obtain a polyurethane prepolymer with terminal isocyanate groups.
[0104] Cool the reaction system to 75°C and add 3 parts by weight. - Glycidyl ether oxypropyltrimethoxysilane and 0.05 parts by weight of dibutyltin dilaurate were stirred at a constant temperature for 30 minutes. After completion, vacuum degassing was carried out for 15 minutes, and the mixture was filled into a sealed container under nitrogen pressure to obtain a polymer composite hot press adhesive.
[0105] Preparation Example 4:
[0106] This preparation example provides a method for preparing an inorganic bubble board core material, including the following steps:
[0107] 100 parts by weight of active magnesium oxide, 100 parts by weight of magnesium sulfate aqueous solution prepared from magnesium sulfate heptahydrate (density of 1.22 g / cm³ at 20℃), 1.2 parts by weight of calcium stearate, 5 parts by weight of alkali-free chopped glass fiber and 2 parts by weight of polyvinyl alcohol were added to a mixer and stirred at 200 r / min for 10 min to obtain the matrix slurry.
[0108] Add 4 parts by weight of 30% hydrogen peroxide aqueous solution to the matrix slurry, continue stirring for 3 minutes, then pour into the mold and let it stand at room temperature for 24 hours to foam and set.
[0109] After demolding, the inorganic bubble board core material is obtained by cutting and processing with a board cutting machine.
[0110] Preparation Example 5:
[0111] This preparation example provides a method for preparing an inorganic bubble board core material, including the following steps:
[0112] 100 parts by weight of active magnesium oxide, 80 parts by weight of magnesium sulfate aqueous solution prepared from magnesium sulfate heptahydrate (density of 1.20 g / cm³ at 20℃), 0.5 parts by weight of calcium stearate, 3 parts by weight of alkali-free chopped glass fiber and 1 part by weight of polyvinyl alcohol were added to a mixer and stirred at 200 r / min for 10 min to obtain the matrix slurry.
[0113] Add 2 parts by weight of 30% hydrogen peroxide aqueous solution to the matrix slurry, continue stirring for 3 minutes, then pour into the mold and let it stand at room temperature for 24 hours to foam and set.
[0114] After demolding, the inorganic bubble board core material is obtained by cutting and processing with a board cutting machine.
[0115] Preparation Example 6:
[0116] This preparation example provides a method for preparing an inorganic bubble board core material, including the following steps:
[0117] 100 parts by weight of active magnesium oxide, 120 parts by weight of magnesium sulfate aqueous solution prepared from magnesium sulfate heptahydrate (density of 1.25 g / cm³ at 20℃), 2.0 parts by weight of calcium stearate, 8 parts by weight of alkali-free chopped glass fiber and 3 parts by weight of polyvinyl alcohol were added to a mixer and stirred at 200 r / min for 10 min to obtain the matrix slurry.
[0118] Add 6 parts by weight of 30% hydrogen peroxide aqueous solution to the matrix slurry, continue stirring for 3 minutes, then pour into the mold and let stand at room temperature for 24 hours to foam and set.
[0119] After demolding, the inorganic bubble board core material is obtained by cutting and processing with a board cutting machine.
[0120] Example 1:
[0121] This embodiment provides an ultrathin metal quick-assembly plate and its forming and preparation method, including the following steps:
[0122] (1) Select aluminum zinc plate or thin aluminum with a thickness of 0.18mm, and use a flexible flip-plate bending machine to cold press and pre-bend both ends of the substrate. Set the over-bending angle of the flip plate relative to the unbent plane to 92.5° for over-bending compensation. After the substrate naturally springs back, it forms a double mother groove structure with a gap of 1.9mm.
[0123] Then, aluminum strips with a cross-sectional thickness of 1.8mm are pushed into the inner gap of the mother groove for filling and support;
[0124] (2) The polymer composite hot-press adhesive obtained in Preparation Example 1 was heated and melted at 120°C using a melt glue machine. The adhesive was then uniformly and synchronously rolled onto the upper and lower surfaces of the inorganic bubble board core material obtained in Preparation Example 4 using a double-sided coating roller. The coating amount on each surface was controlled at 100 g / m².
[0125] (3) The aluminum-zinc coated steel plate or thin aluminum plate with double mother groove formed in step (1) is laid flat on the front side of the inorganic bubble board core, and a 0.05mm thick balancing aluminum foil is laid flat on its back side. The three-layer structure is simultaneously fed into the flat hot press and held under pressure for 12s at a surface temperature of 120℃ and a pressure of 1.2MPa.
[0126] (4) Immediately after demolding, the mold enters the cold pressing correction station. Circulating cooling water at 20°C is introduced into the cold pressing mold, and a pressure of 1.5MPa is applied and cold pressing is performed for 8 seconds to allow the adhesive layer to crystallize rapidly, generate initial tack strength, and correct the overall tolerance to obtain the molded board.
[0127] (5) At an ambient temperature of 25°C, a 0.15mm thick polyvinyl chloride decorative film is applied to the front of the cold-pressed and shaped aluminized zinc plate or thin aluminum using a PUR coating process.
[0128] (6) Place the wrapped quick-release plate flat on a pallet and transfer it to a normal temperature warehouse with an ambient temperature of 25°C and a relative humidity of 55%. Store it naturally for 11 hours to allow the internal adhesive to continue to cross-link and cure under moisture and form a stable bonding structure, thus obtaining the ultra-thin metal quick-release plate.
[0129] Example 2:
[0130] This embodiment provides an ultrathin metal quick-assembly plate and its forming and preparation method, including the following steps:
[0131] (1) Select an aluminum-zinc plated substrate with a thickness of 0.18mm, and use a flexible flip-plate bending machine to cold press and pre-bend the two ends of the aluminum-zinc plated substrate or thin aluminum. Set the over-bending angle of the flip plate relative to the unbent plane to 92° for over-bending compensation. After the substrate naturally springs back, it forms a double mother groove structure with a gap of 1.8mm.
[0132] Then, aluminum strips with a cross-sectional thickness of 1.7mm are pushed into the inner gap of the mother groove for filling and support;
[0133] (2) The polymer composite hot-press adhesive obtained in Preparation Example 2 was heated and melted at 110°C using a melt glue machine. The adhesive was then uniformly and synchronously rolled onto the upper and lower surfaces of the inorganic bubble board core material obtained in Preparation Example 5 using a double-sided coating roller. The coating amount on each surface was controlled at 80 g / m².
[0134] (3) The aluminum-zinc plate or thin aluminum plate with double mother groove formed in step (1) is laid flat on the front side of the inorganic bubble board core, and a balancing aluminum foil with a thickness of 0.03mm is laid flat on its back side. The three-layer structure is simultaneously fed into the flat hot press and held under pressure for 10s at a surface temperature of 110℃ and a pressure of 0.8MPa.
[0135] (4) Immediately after demolding, the mold enters the cold pressing correction station. The cold pressing mold is filled with circulating cooling water at 15°C, and a pressure of 1.0MPa is applied and cold pressing is performed for 5 seconds to allow the adhesive layer to crystallize rapidly, generate initial tack strength, and correct the overall tolerance to obtain the molded board.
[0136] (5) At an ambient temperature of 20°C, a 0.12 mm thick polyvinyl chloride decorative film is coated on the front side of the cold-pressed substrate using a PUR coating process.
[0137] (6) Place the wrapped quick-release plate flat on a pallet and transfer it to a normal temperature warehouse with an ambient temperature of 15°C and a relative humidity of 40% for 12 hours to allow the internal adhesive to continue to cross-link and cure under moisture and form a stable bonding structure, thus obtaining the ultra-thin metal quick-release plate.
[0138] Example 3:
[0139] This embodiment provides an ultrathin metal quick-assembly plate and its forming and preparation method, including the following steps:
[0140] (1) Select aluminum-zinc coated steel plate or thin aluminum with a thickness of 0.18mm, and use a flexible flip-plate bending machine to cold press and pre-bend the two ends of the substrate. Set the over-bending angle of the flip plate relative to the unbent plane to 93° for over-bending compensation. After the substrate naturally springs back, it forms a double mother groove structure with a gap of 2.0mm.
[0141] Then, aluminum strips with a cross-sectional thickness of 1.9mm are pushed into the inner gap of the mother groove for filling and support;
[0142] (2) The polymer composite hot-press adhesive obtained in Preparation Example 3 was heated and melted at 130°C using a melt glue machine. The adhesive was then uniformly and synchronously rolled onto the upper and lower surfaces of the inorganic bubble board core material obtained in Preparation Example 6 using a double-sided coating roller. The coating amount on each surface was controlled at 120 g / m².
[0143] (3) The aluminum-zinc coated steel plate or thin aluminum plate with double mother groove formed in step (1) is laid flat on the front side of the inorganic bubble board core, and a balancing aluminum foil with a thickness of 0.08mm is laid flat on its back side. The three-layer structure is simultaneously fed into the flat hot press and held under pressure for 15s at a surface temperature of 130℃ and a pressure of 1.5MPa.
[0144] (4) Immediately after demolding, the mold enters the cold pressing and correction station. The cold pressing mold is filled with 25°C circulating cooling water, and a pressure of 2.0MPa is applied and cold pressing is performed for 10s to make the adhesive layer crystallize rapidly to generate initial tack strength and correct the overall tolerance, thus obtaining the molded board.
[0145] (5) At an ambient temperature of 30°C, a polyvinyl chloride decorative film with a thickness of 0.18 mm is coated on the front side of the cold-pressed substrate using a PUR coating process.
[0146] (6) Place the wrapped quick-release plate flat on a pallet and transfer it to a normal temperature warehouse with an ambient temperature of 35°C and a relative humidity of 70% for 10 hours to allow the internal adhesive to continue to cross-link and cure under moisture and form a stable bonding structure, thus obtaining the ultra-thin metal quick-release plate.
[0147] Example 4:
[0148] This embodiment provides an ultrathin metal quick-assembly plate and its forming and preparation method, including the following steps:
[0149] (1) Select an aluminum-zinc plated substrate with a thickness of 0.18mm, and use a flexible flip-plate bending machine to cold press and pre-bend both ends of the substrate. Set the over-bending angle of the flip plate relative to the unbent plane to 92.5° for over-bending compensation. After the substrate naturally springs back, it forms a double mother groove structure with a gap of 1.9mm.
[0150] Then, aluminum strips with a cross-sectional thickness of 1.8mm are pushed into the inner gap of the mother groove for filling and support;
[0151] (2) The polymer composite hot-press adhesive obtained in Preparation Example 1 was heated and melted at 125°C using a melt glue machine. The adhesive was then uniformly and synchronously rolled onto the upper and lower surfaces of the inorganic bubble board core material obtained in Preparation Example 4 using a double-sided coating roller. The coating amount on each surface was controlled at 90 g / m².
[0152] (3) The aluminum-zinc coated steel plate or thin aluminum plate with double mother groove formed in step (1) is laid flat on the front side of the inorganic bubble board core, and a balancing aluminum foil with a thickness of 0.04 mm is laid flat on its back side. The three-layer structure is simultaneously fed into a flat hot press and held under pressure for 14 s at a surface temperature of 115℃ and a pressure of 1.0 MPa.
[0153] (4) Immediately after demolding, the mold enters the cold pressing and correction station. The cold pressing mold is circulated with 18°C cooling water, pressure is applied at 1.2MPa and cold pressing is performed for 7s to make the adhesive layer crystallize rapidly to generate initial tack strength and correct the overall tolerance, thus obtaining the molded board.
[0154] (5) At an ambient temperature of 22°C, a 0.15 mm thick polyvinyl chloride decorative film is coated on the front side of the cold-pressed substrate using a PUR coating process.
[0155] (6) Place the wrapped quick-release plate flat on a pallet and transfer it to a normal temperature warehouse with an ambient temperature of 20°C and a relative humidity of 60%. Store it naturally for 12 hours to allow the internal adhesive to continue to cross-link and cure under moisture and form a stable bonding structure, thus obtaining the ultra-thin metal quick-release plate.
[0156] Comparative Example 1:
[0157] Compared with Example 1, the difference is that in step (1), no over-bending compensation is set. Instead, the angle of the flap relative to the unbent plane is set to 90° for cold pressing pre-bending. All other aspects are the same.
[0158] Comparative Example 2:
[0159] Compared with Example 1, the difference is that in step (3), an asymmetric composite method is used. First, the aluminum-zinc coated steel plate or thin aluminum with double mother groove is laid flat on the front of the inorganic bubble board core for hot pressing and pressure holding. After demolding, the balancing aluminum foil is laid flat on its back for secondary hot pressing and composite. The rest are the same.
[0160] Comparative Example 3:
[0161] Compared with Example 1, the difference is that step (4) is removed. That is, after hot pressing demolding in step (3), forced cold pressing and shaping and correction are not performed. Instead, step (5) is directly entered for room temperature wrapping. All other steps are the same.
[0162] Comparative Example 4:
[0163] Compared with Example 1, the difference is that in step (2), the self-made polymer composite hot-press adhesive is replaced with commercially available conventional non-reactive ethylene-vinyl acetate copolymer hot melt adhesive, and the natural storage cross-linking curing process in step (6) is removed, while the rest are the same.
[0164] Comparative Example 5:
[0165] Compared with Example 1, the difference is that the double mother groove structure is processed by the traditional multi-pass cold bending and rolling forming process in step (1), while the rest are the same.
[0166] Test Example 1:
[0167] (1) Take 10 mg of each of the polymer composite hot press adhesive samples obtained in Preparation Examples 1 to 3 and place them in the standard aluminum crucible of the differential scanning calorimeter. Heat them to 130 °C at a heating rate of 10 °C / min under a nitrogen atmosphere and hold them at the temperature for 5 min to eliminate thermal history. Then cool them continuously to 10 °C at a cooling rate of 10 °C / min. Record the heat flow curve during the cooling stage and extract the crystallization peak temperature and crystallization enthalpy change.
[0168] (2) Take the adhesive layer sample at the moment of cold pressing and demolding in step (4) of Examples 1 to 3 (recorded as 0h), and the adhesive layer sample after being stored for the natural storage time specified in each example in step (6).
[0169] The above samples were scanned using a Fourier transform infrared spectrometer with an attenuated total reflection accessory. The scanning range was 4000 cm⁻¹ to 400 cm⁻¹, the resolution was 4 cm⁻¹, and the number of scans was 32.
[0170] The absorbance of the nearby internal standard peaks is expressed as the ratio of their absorbances. The isocyanate group's relative absorbance was used as the basis for calculating the isocyanate group conversion rate based on the change in relative absorbance before and after natural storage.
[0171] Table 1. Thermal analysis and functional group conversion rate test results of polymer composite hot-pressed adhesives
[0172] Group Crystallization peak temperature / ℃ Enthalpy change of crystallization / -1 Relative absorbance of isocyanate groups after 0h of cold pressing and demolding Relative absorbance of isocyanate groups after specified storage time Isocyanate group conversion rate during storage / % Preparation Example 1 / Example 1 42.3 36.7 0.862 0.031 96.4 Preparation Example 2 / Example 2 41.1 31.4 0.881 0.045 94.9 Preparation Example 3 / Example 3 43.8 39.2 0.814 0.021 97.4
[0173] According to Table 1 and Figure 1 According to the data, the polymer composite hot-pressed adhesives prepared in Examples 1 to 3 all exhibited exothermic crystallization peaks in the temperature range of 41°C to 44°C under a cooling rate of 10°C / min, and the enthalpy change of crystallization was at 31.4°C. -1 to 39.2 Between -1 and 1.
[0174] This indicates that the polycaprolactone segments in the system possess the physical property of undergoing a phase transition at a specific temperature threshold.
[0175] Combining the temperature parameters of the cold pressing station in the molding preparation method, the liquid adhesive layer under hot pressing condition rapidly cools down and enters the crystallization temperature zone of polycaprolactone segments after contacting the mold with circulating cooling water at 15℃ to 25℃. This promotes the regular arrangement of macromolecular segments and the formation of a crystalline physical cross-linked structure, thereby establishing initial mechanical strength and maintaining the molding tolerance of the sheet during the demolding stage.
[0176] The absorbance values of the characteristic peaks in the infrared spectrum show that, in the state of 0h after cold pressing and demolding, the adhesive layers of Examples 1 to 3 retain a high concentration of isocyanate groups.
[0177] After being stored naturally at the specified ambient temperature, relative humidity, and time according to each embodiment, the characteristic absorption peak of the isocyanate group decayed, and the conversion rate reached over 94%.
[0178] This indicates that the adhesive reacts with the moisture contained in the inorganic core material under macroscopic stacking conditions, and the isocyanate groups continue to transform during natural storage, gradually forming a cross-linked structure;
[0179] By combining crystallization phase transformation shaping with subsequent moisture crosslinking, the coupling relationship between hot pressing holding time and subsequent chemical crosslinking process in continuous production is weakened.
[0180] Test Example 2:
[0181] (1) Select the aluminum-zinc plate or thin aluminum and the balanced aluminum foil used in Examples 1 to 4 and Comparative Example 2. Clean the oil and impurities from the outer surface of the aluminum-zinc plate or thin aluminum and the outer surface of the aluminum foil.
[0182] (2) Use high temperature resistant test adhesive to attach foil high temperature resistance strain gauges to the geometric center positions of the outer surface of the aluminum zinc plate or thin aluminum and the outer surface of the balance aluminum foil.
[0183] Each strain gauge is connected to a multi-channel dynamic strain gauge via shielded wires, with a sampling frequency set to 50Hz. A clearance structure is installed at the corresponding positions of the hot-pressing plate, strain gauges, and shielded wires to prevent direct compression of the strain gauges and shielded wires during the hot-pressing process.
[0184] (3) Perform the sheet metal composite operation according to the process parameters set in Examples 1 to 4 and Comparative Example 2. For Examples 1 to 4, the instant when the synchronous hot pressing ends and the sheet metal leaves the hot press is taken as the zero point of time;
[0185] For Comparative Example 2, the moment the second hot-pressing composite ends and the plate leaves the hot press is taken as the zero point of time.
[0186] Continuously record the thermal strain data of the front and back sides throughout the entire process from cold pressing and shaping to demolding.
[0187] (4) Extract the maximum shrinkage strain values of the front metal layer and the back metal layer of each group of samples during the entire cooling and setting cycle, and calculate the absolute shrinkage strain difference between the two.
[0188] Table 2. Test results of maximum shrinkage strain on both sides during the sheet forming process.
[0189] Group Maximum shrinkage strain of front aluminized zinc plate / Maximum shrinkage strain of back-side balanced aluminum foil / Absolute contraction strain difference / Example 1 -1254.6 -1268.2 13.6 Example 2 -1102.3 -1089.8 12.5 Example 3 -1431.7 -1452.4 20.7 Example 4 -1187.1 -1169.5 17.6 Comparative Example 2 -1275.4 -214.9 1060.5
[0190] According to Table 2 and Figure 2 Based on the data from Examples 1 to 4, the maximum shrinkage strain difference between the front aluminized zinc-coated steel or thin aluminum sheet and the back balancing aluminum foil during the entire cooling and setting cycle is distributed within 12.5. Up to 20.7 Between them, the contraction strain curves on both sides are basically synchronized and overlap.
[0191] This indicates that through the processing method of simultaneous hot pressing and forced cold pressing, the upper and lower metal surfaces of the sheet undergo simultaneous heating and cooling processes, and the trend of shrinkage strain and deformation amplitude remain highly consistent.
[0192] Comparative Example 2 employs an asymmetric secondary hot-pressing composite process, achieving an absolute shrinkage strain difference of 1060.5 between the front and back sides. There is a significant difference in shrinkage deformation between the front and back metal layers.
[0193] During the process of the sheet material transitioning from a hot-pressed state to a cooled and shaped state, the interface between the two materials generates interfacial tangential shear stress due to the difference in heating state and expansion coefficient.
[0194] In Examples 1 to 4, the shrinkage deformation of the front metal layer and the back metal layer has a high degree of coordination, which reduces the strain difference and unbalanced bending effect at the interface on both sides of the core material, maintains the deformation coordination of the composite structure, and thus suppresses the macroscopic bow-shaped warping of the plate caused by uneven distribution of internal residual stress.
[0195] Test Example 3:
[0196] (1) From the preparation process of Examples 1 to 4, Comparative Example 1 and Comparative Example 5, cut out the aluminum-zinc plate or thin aluminum sample with double mother groove structure after the molding process of step (1) and clean the surface.
[0197] (2) Use a two-dimensional image measuring instrument to scan the cross-section of the bending area of the sample section and extract the actual forming inner angle value.
[0198] Eight measuring points were evenly distributed along the length of the mother groove. The groove gap width was measured using a digital vernier caliper, and the average gap value was recorded. An on-site assembly test was conducted using aluminum profiles of the corresponding specifications, and the assembly status was recorded.
[0199] (3) Prepare cross-sectional measurement samples along the bending area of the substrate. Use a two-dimensional image measuring instrument to measure the thickness of the metal layer at the outer radius of the bend. Measure 5 points in each sample segment and record the lowest residual thickness. Combined with the original substrate thickness of 0.18 mm, calculate the thickness reduction rate at the bend position.
[0200] Table 3 Test results of sheet forming accuracy and mother groove dimensional stability
[0201] Group Actual formed interior angle / ° Average gap of the slot / mm Aluminum strip assembly status Minimum residual thickness at the bend / mm Thickness reduction rate / % Example 1 89.8 1.89 Smooth insertion with even spacing 0.176 2.2 Example 2 90.3 1.82 Smooth insertion with even spacing 0.177 1.7 Example 3 89.7 1.97 Smooth insertion with even spacing 0.175 2.8 Example 4 90.1 1.91 Smooth insertion with even spacing 0.176 2.2 Comparative Example 1 92.6 2.45 Severely loose and cannot be secured. 0.174 3.3 Comparative Example 5 90.4 1.94 Smooth loading, with occasional stutters. 0.141 21.7
[0202] According to Table 3 and Figure 3 According to the data, the actual forming inner angle of Examples 1 to 4 is controlled between 89.7° and 90.3°, the average gap of the groove is maintained in the range of 1.82mm to 1.97mm, and a sliding assembly tolerance of about 0.1mm is formed with the corresponding aluminum strip.
[0203] Comparative Example 1 was formed directly without setting over-bending compensation. Its inner angle rebounded to 92.6° due to the release of internal stress of the high-tensile thin steel plate, causing the groove gap to open outward to 2.45mm, causing the aluminum strip to loosen in the groove and lose its structural support function.
[0204] By setting the bending angle of the flap relative to the unbent plane to 92° to 93°, the bending inner angle before unloading is less than 90°, thereby reserving compensation for the elastic rebound of the material after unloading.
[0205] After the material is unloaded, it springs back to a vertical state of nearly 90°, which reduces the impact of residual stress in the forming zone on the groove size and achieves dimensional stability of the double mother groove structure.
[0206] Regarding wall thickness, the thickness reduction rates of Examples 1 to 4 were at a low level of 1.7% to 2.8%. Comparative Example 5, which employed a multi-pass cold bending and rolling process, achieved a thickness reduction rate of 21.7% in the corner area, with the residual thickness decreasing to 0.141 mm.
[0207] The flexible flip-type bending machine applies surface contact wrapping pressure to the sheet metal during operation and flips it along the bending axis. The material is mainly subjected to pure bending stress.
[0208] Traditional roll forming relies on the line contact friction of multiple sets of rollers to drive the sheet forward. The corner positions are subjected to complex shear and tensile stresses, resulting in the accumulation of tensile deformation in the corner areas and significant wall thickness reduction.
[0209] The flexible flipping and folding process can reduce the thickness loss in the folded area and maintain the structural integrity of the aluminum zinc coating and the substrate.
[0210] Test Example 4:
[0211] (1) The molded plates of Examples 1 to 4, Comparative Example 2 and Comparative Example 3, which have completed all preparation processes, were selected as test objects. Each group of test plates was placed horizontally on a standard marble testing platform and allowed to stand for 24 hours under the conditions of ambient temperature of 20°C and relative humidity of 50% to release the instantaneous stress inside the plate.
[0212] (2) Using a laser flatness measuring instrument combined with a high-precision feeler gauge, multi-point scanning measurements were performed along the longitudinal centerline and two diagonal directions of the plate, and the contour elevation data on each measurement path were recorded.
[0213] (3) Calculate the maximum chord height difference of each group of boards within the length of each meter as the straightness deviation index, and extract the elevation difference between the highest and lowest points within the whole board as the maximum warping deformation.
[0214] Table 4. Test results of macroscopic flatness and warping deformation of the large board.
[0215] Group Maximum chord height difference along longitudinal centerline / mm Maximum chord height difference along the diagonal / mm Maximum warping deformation of the entire board / mm Macroscopic morphology assessment Example 1 0.08 0.09 0.12 flat Example 2 0.06 0.07 0.10 flat Example 3 0.09 0.11 0.14 flat Example 4 0.07 0.08 0.11 flat Comparative Example 2 1.85 2.13 3.42 Obvious arch-shaped warping Comparative Example 3 0.94 1.15 1.58 Local wavy undulations
[0216] According to Table 4 and Figure 4 According to the data, the maximum chord height difference of the boards in Examples 1 to 4 is no higher than 0.11mm in both the longitudinal centerline and diagonal direction, the maximum warping deformation of the whole board is maintained in the range of 0.10mm to 0.14mm, and the macroscopic shape remains straight.
[0217] Comparative Example 2 uses an asymmetric composite molding process, with a maximum chord height difference of 1.85mm along its longitudinal centerline and a warping of more than 3.4mm.
[0218] Because the metal panel and the base foil accumulate asymmetrical thermal strain during the stepwise heating and pressurization stage, the difference in the thermal expansion coefficients of the heterogeneous materials during the cooling process generates unbalanced tangential shear stress at the interface of the inorganic core material, causing the plate to undergo macroscopic bow-shaped bending towards the side with greater stress.
[0219] Comparative Example 3 omits the cold pressing step after hot pressing composite, and its diagonal chord height difference reaches 1.15mm.
[0220] When the sheet leaves the hot press, the polycaprolactone segments in the adhesive layer are in a molten state, and the adhesive layer has not yet formed the initial shaped structure produced by the crystallization of the polycaprolactone segments.
[0221] When the board is freed from external mechanical constraints, the thermally expanded metal layer shrinks during natural cooling. At this time, the adhesive layer has not yet formed a stable crystalline structure, making it difficult to fully restrict the relative displacement between the metal panel and the porous core material, resulting in interface slippage and local undulations in the panel.
[0222] The continuous synchronous hot pressing in the embodiment ensures that the front metal layer and the back metal layer maintain a relatively coordinated thermal deformation process.
[0223] Subsequently, the composite board is rapidly cooled using a cold pressing mold, allowing the polycaprolactone segments in the adhesive layer to enter the crystallization temperature range and form a crystalline physical cross-linked structure. This provides initial mechanical strength to resist interfacial slippage and local deformation during the subsequent moisture cross-linking process, thereby maintaining the geometrical stability of the board after it transitions from a hot-pressed state to a room temperature state.
[0224] Test Example 5:
[0225] (1) Take the molded plates prepared by the process of Examples 1 to 4 and Comparative Example 4, and cut them into standard peel test strips with a width of 25 mm and a length of 150 mm using a band saw.
[0226] The spline was divided into an initial test group and an aging test group.
[0227] (2) Fix the initial test group of the sample onto the fixture of the universal testing machine.
[0228] The tensile speed was set to 50 mm / min, and the test was conducted using the 90° peel test method.
[0229] Record the load-displacement curves during the peeling process, divide the average force value of the peeling platform area by the spline width, calculate the initial interface peeling strength, and observe and record the failure mode of the interface.
[0230] (3) Place the aging test group samples in a high and low temperature alternating damp heat test chamber.
[0231] The single cycle program was set as follows: maintain at -20℃ for 2 hours, uniformly increase the temperature to 60℃ within 30 minutes, adjust the relative humidity to 90% and maintain it for 2 hours, then cool down to -20℃ within 30 minutes. After 20 consecutive alternating cycles, the sample was removed and placed in a room temperature environment for 2 hours to allow it to return to thermal equilibrium.
[0232] (4) Perform a 90-degree peel test on the aging test group samples according to the same parameters and methods as in step (2).
[0233] Extract the interface peel strength after aging, calculate the attenuation rate relative to the initial strength, and record the corresponding interface failure mode.
[0234] Table 5 Results of interfacial peel strength and high and low temperature weathering resistance tests
[0235] Group Initial peel strength / Peel strength after aging / Intensity attenuation rate / % Aging-related interface degradation mode Example 1 3.86 3.73 3.4 Core material cohesive failure Example 2 3.62 3.45 4.7 Core material cohesive failure Example 3 4.15 3.97 4.3 Core material cohesive failure Example 4 3.78 3.54 6.4 Core material cohesive failure Comparative Example 4 2.34 0.73 68.8 Metal interface degumming
[0236] According to Table 5 and Figure 5 The data shows that the initial interfacial peel strength distribution in Examples 1 to 4 is 3.62. -1 to 4.15 Between -1 and 20 cycles of high and low temperature damp heat, the attenuation rate of peel strength was controlled in the low range of 3.4% to 6.4%, and the failure mode of the test specimens was cohesive failure within the inorganic bubble board core material.
[0237] This indicates that after using a polymer composite hot-press adhesive and a delayed natural curing process, the polyurethane prepolymer reacts with isocyanate groups and moisture to form a three-dimensional cross-linked network.
[0238] The system contains γ-glycidyl etheroxypropyltrimethoxysilane coupling agent, whose trimethoxysilane end hydrolyzes to form silanol groups. The silanol groups condense with the hydroxyl groups on the surface of the metal oxide layer and the inorganic plate, and form a siloxane-bonded structure at the interface.
[0239] Its epoxy functional groups can improve the compatibility between silane coupling agents and polyurethane organic phases, thereby enhancing the interfacial connection between organic adhesive layers and inorganic substrates.
[0240] This interfacial bonding structure can resist the interfacial tangential deformation caused by changes in temperature and humidity. After aging, all samples showed cohesive failure of the core material, indicating that the interfacial bonding strength between the adhesive layer and the substrate is not lower than the load-bearing strength when the core material undergoes cohesive failure under the test conditions.
[0241] Comparative Example 4 used a commercially available non-reactive ethylene-vinyl acetate copolymer hot melt adhesive, and the post-curing crosslinking process was omitted. Its initial peel strength was 2.34. -1, after aging cycles, the peel strength decreased significantly to 0.73. -1, the attenuation rate reached 68.8%, and the failure mode was manifested as debonding at the interface between the adhesive layer and the metal surface.
[0242] This is because non-reactive hot melt adhesives rely on the physical anchoring of intermolecular van der Waals forces with the surface morphology of the substrate to form a bond. These thermoplastic materials soften at high temperatures of 60°C, resulting in a decrease in cohesion, and shrink and become brittle at low temperatures of -20°C. Repeated phase transitions and volume shrinkage cause interface defects to gradually accumulate, weakening the original physical adhesion and intermolecular interactions, ultimately leading to interfacial debonding between the adhesive layer and the metal surface.
[0243] By introducing reactive polyurethane adhesive and cross-linking mechanism, the interfacial bonding durability and structural stability of composite panels under varying temperature and humidity conditions are improved.
[0244] Test Example 6:
[0245] (1) A molding production line using the continuous preparation process corresponding to Examples 1 to 4 was set as the test group, and a conventional process production line using conventional reactive polyurethane hot melt adhesive and requiring continuous pressure and flat placement on the production line until the adhesive layer forms an initial bonding strength that meets the transfer requirements was set as the comparative example 6.
[0246] We selected a standard-sized (1220mm×2440mm) ultra-thin metal quick-release plate and calculated the time occupied by the main equipment and the space occupied by the curing process for different preparation processes.
[0247] (2) Based on the time of hot pressing, cold pressing, continuous pressure flat laying and plate transfer in each group of processes, calculate the time required for a single plate from entering the hot press station until leaving the cold pressing station or continuous pressure station and completely releasing the main line machinery equipment. Define this time as the main line equipment occupation time for a single plate.
[0248] (3) Use 1,000 finished boards as a unified calculation benchmark for the space occupied by different curing processes.
[0249] Based on the pallet stacking method of the embodiment group and the single-layer flat placement method of Comparative Example 6, the projected area of the workshop floor space occupied by the above 1,000 finished boards during the storage process of approximately 10 to 12 hours for continued cross-linking and curing is calculated.
[0250] According to the preparation process, the sample was flattened and placed on a standard pallet and transferred to a room temperature warehouse for three-dimensional storage. The sample 6, on the other hand, required a single-layer flat conveyor belt and a buffer rack array for planar extension and stagnation.
[0251] Table 6 Test Results of Mainline Equipment Occupancy Time and Solidification Process Space Occupancy
[0252] Group Single sheet main line equipment occupancy time / s Single accounting benchmark / sheet Unified Calculation Standard / Zhang Curing process accounting for workshop area occupied / m² Example 1 21.4 1 1000 45.6 Example 2 16.3 1 1000 42.1 Example 3 26.8 1 1000 48.3 Example 4 22.5 1 1000 46.2 Comparative Example 6 1854.2 1 1000 3452.8
[0253] According to the calculation results in Table 6, the time occupied by the main equipment for a single sheet of board in Examples 1 to 4 is 16.3s to 26.8s; when 1000 sheets of board are used as a unified calculation benchmark, the workshop floor area occupied by the crosslinking and curing process is 42.1m² to 48.3m².
[0254] Comparative Example 6, due to the use of conventional process flow, requires a long time to occupy the main line mechanical structure for pressurization and flattening after the board enters the composite process, until the reactive adhesive forms the initial bonding strength that meets the transfer requirements, resulting in the main line equipment occupancy time of a single board reaching 1854.2s;
[0255] Furthermore, since the adhesive layer has a weak ability to limit the deformation caused by the self-weight of the board and the release of internal stress before it forms a stable initial bonding strength, the finished board needs to be kept flat in a single layer on the conveyor belt or in a flat buffer area. When 1,000 boards are used as a unified calculation benchmark, the workshop planar projection area occupied by the curing process is 3,452.8 m².
[0256] The continuous preparation process of this invention relies on the phase change characteristics of a specifically synthesized polycaprolactone-modified polyurethane adhesive. In a forced cold pressing process of a few seconds to a dozen seconds, the system is rapidly cooled by circulating cooling water, which promotes the crystallization and precipitation of soft segments and the formation of a physically shaped structure, giving the board an initial bonding strength that resists interfacial slippage and cooling deformation.
[0257] This initial mechanical locking structure formed by crystallization reduces the coupling relationship between the subsequent chemical crosslinking process and the time occupied by the main equipment in traditional processes.
[0258] After being shaped, the sheets can be palletized after leaving the main line equipment and continue to complete the moisture crosslinking process under normal temperature storage conditions, thereby shortening the time that a single sheet occupies the main line equipment and reducing the workshop floor space required for the curing process.
[0259] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. An ultra-thin metal quick-release plate, characterized in that, From top to bottom, it includes a polyvinyl chloride decorative film layer, an aluminum-zinc plate or thin aluminum layer, an upper adhesive layer, an inorganic bubble board core material layer, a lower adhesive layer, and a balancing aluminum foil layer. Both the upper and lower adhesive layers are made of a polymeric composite hot-press adhesive with initial tack and moisture-curing crosslinking properties. The polymeric composite hot-press adhesive is made from raw materials comprising the following parts by weight: Polypropylene glycol: 30-40 parts; Polycaprolactone diol: 20-30 parts; 4'-Diphenylmethane diisocyanate: 15-25 parts; - Glycidyl etheroxypropyltrimethoxysilane: 1-3 parts; Dibutyltin dilaurate: 0.01 to 0.05 parts.
2. The ultra-thin metal quick-release plate according to claim 1, characterized in that, The polymer composite hot-press adhesive is prepared by the following method: The specified weight proportions of polypropylene glycol and polycaprolactone glycol are mixed and dehydrated under vacuum conditions; Subsequently, under nitrogen protection, the specified weight of 4,4'-diphenylmethane diisocyanate was added and reacted at a constant temperature to obtain a polyurethane prepolymer with isocyanate-terminated groups. Add the stated weight percentage after cooling. - Glycidyl etheroxypropyltrimethoxysilane and dibutyltin dilaurate were prepared by constant temperature stirring and vacuum degassing.
3. The ultra-thin metal quick-release plate according to claim 1, characterized in that, The two ends of the aluminized zinc plate or thin aluminum layer are provided with a double mother groove structure formed by pre-bending inward and naturally rebounding, and the inner gap of the double mother groove structure is filled with aluminum strips.
4. The ultra-thin metal quick-release plate according to claim 4, characterized in that, The thickness of the aluminized zinc plate or thin aluminum layer is 0.18 mm, the gap of the double female groove structure is 1.8 to 2.0 mm, and the cross-sectional thickness of the aluminum strip is 1.7 to 1.9 mm.
5. A method for forming and preparing an ultra-thin metal quick-assembly plate, comprising the ultra-thin metal quick-assembly plate according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Cold press and pre-bend both ends of the aluminum-zinc plate or thin aluminum, and after springback, form a double female groove structure. Push the aluminum strip into the inner gap of the double female groove structure to fill it. S2. Heat and melt the polymer composite hot-press adhesive, and simultaneously roll the adhesive onto the upper and lower surfaces of the inorganic bubble board core material. S3. Lay the aluminum-zinc plate or thin aluminum plate processed in step S1 on the front side of the inorganic bubble board core material, lay the balancing aluminum foil on the back side of the inorganic bubble board core material, and simultaneously send them into the flat plate hot press for pressure holding hot pressing composite. S4. After demolding, it enters the cold pressing station and is cold-pressed and shaped by a cold pressing mold with circulating cooling water. S5. Apply a polyvinyl chloride decorative film to the front of the cold-pressed and shaped aluminized zinc plate or thin aluminum using a PUR coating process. S6. Stack the coated boards and transfer them to a room temperature environment for storage to allow for internal moisture cross-linking and curing.
6. The method for forming and preparing an ultrathin metal quick-assembly plate according to claim 5, characterized in that, In step S1, a flexible flip-plate bending machine is used for cold pre-bending. The bending angle of the flip plate of the bending machine relative to the unbent plane is set to 92°~93°.
7. The method for forming and preparing an ultrathin metal quick-assembly plate according to claim 5, characterized in that, In step S2, the heating and melting temperature of the polymer composite hot-press adhesive is 110~130℃, and the coating amount on each surface is controlled at 80~120g / m². In step S3, the surface temperature of the hot platen of the flat platen hot press is 110~130℃, the applied pressure is 0.8~1.5MPa, and the holding time is 10~15s.
8. The method for forming and preparing an ultra-thin metal quick-assembly plate according to claim 5, characterized in that, In step S4, the temperature of the circulating cooling water introduced into the cold pressing mold is 15~25℃, the pressure applied at the cold pressing station is 1.0~2.0MPa, and the cold pressing time is 5~10s.
9. The method for forming and preparing an ultra-thin metal quick-assembly plate according to claim 5, characterized in that, In step S6, the temperature of the storage environment is controlled at 15~35℃, the relative humidity is controlled at 40%~70%, and the storage time is 10~12h.